2016
DOI: 10.21511/imfi.13(3).2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the marketing of professional services

Abstract: This study explores the marketing in a multinational professional services organization and attempts to identify marketing factors relevant to the organization. The main objective is to identify critical factors that influence the successful marketing of professional services. To accomplish this objective, research is undertaken as a case study with a quantitative survey of employees from the professional services organization. The main finding was that the 7P framework (product/service, price, place, promotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Familiarity with marketing trends and methodologies can both improve decision-making process regarding the choice of marketing mode and style best suited to management consulting service businesses and help to identify client needs and enhance the delivery of value adding services. Enerson et al (2016) suggest that current and future marketing directions will affect the way that the professional service marketing is formulated and implemented. The authors believe that in the professional environment, service organizations that have a clear marketing direction will have more chance of succeeding.…”
Section: Marketing Of Management Consulting Firmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Familiarity with marketing trends and methodologies can both improve decision-making process regarding the choice of marketing mode and style best suited to management consulting service businesses and help to identify client needs and enhance the delivery of value adding services. Enerson et al (2016) suggest that current and future marketing directions will affect the way that the professional service marketing is formulated and implemented. The authors believe that in the professional environment, service organizations that have a clear marketing direction will have more chance of succeeding.…”
Section: Marketing Of Management Consulting Firmsmentioning
confidence: 99%
“…Enerson et al (2016) suggest that current and future marketing directions will affect the way that the professional service marketing is formulated and implemented. The authors believe that in the professional environment, service organizations that have a clear marketing direction will have more chance of succeeding.…”
Section: Marketing Of Management Consulting Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan and Chew (2010) investigated the marketing strategy, business environment and performance of construction SMEs in China, and found that marketing differentiation and innovation helps construction SMEs to achieve superior performance, but reported a negative relationship between competitive pressure and construction SMEs' performance. Enerson et al (2016) carried out a study aimed at identifying the critical factors that influence the marketing of professional services in the South African construction industry.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Musa et al (2016) identified three factors that influence the choice of marketing strategy, and these are the entrepreneur's attitude and knowledge, technical knowledge of the firm, and branding strategy. Enerson et al (2016) proposed a framework of 7P (product/service, price, place, promotion, physical evidence, people, and process); which influences the marketing of professional services. The study found out that place, physical evidence and product components are most critical, and that promotion and price are least critical.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%